If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = 5m + 20m + -2m Combine like terms: 5m + 20m = 25m -13 = 25m + -2m Combine like terms: 25m + -2m = 23m -13 = 23m Solving -13 = 23m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-23m' to each side of the equation. -13 + -23m = 23m + -23m Combine like terms: 23m + -23m = 0 -13 + -23m = 0 Add '13' to each side of the equation. -13 + 13 + -23m = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -23m = 0 + 13 -23m = 0 + 13 Combine like terms: 0 + 13 = 13 -23m = 13 Divide each side by '-23'. m = -0.5652173913 Simplifying m = -0.5652173913
| -2=x^2-5x+2 | | X(.10)+x=1375 | | 11w-3(2-6w)=81 | | 1+5d=11 | | 4w^2+6w-7=0 | | 2x+6=21-3 | | 2x-x+5x-9= | | 0.6a+5-0.3a-7= | | 2y-3.5=6.5 | | 5z=2.9+3.6 | | m^2+3m-3=0 | | 0=y^2+2y-96 | | 5=5-5t | | 3x-21=5x-5 | | -4x+-4-9=-12x+11 | | 35=8-9y | | -p^2-2p=0 | | 2(j-7)=64 | | 3y-8=9 | | 2x+4(x+3)=36 | | 4e^3x+6=30 | | -3x-3x=26-2 | | 8c-13=3c+36 | | 2u^2-3u=0 | | -9=k-5k+7 | | 4x^2-15=25 | | 6t+17-3t=38 | | -6w+14=-76 | | 11x+22x-2y+54y= | | 0.5a-5-0.5a= | | -f^2+5f=0 | | 3-8p=29 |